Sonographic diagnosis of anatomical variations associated with carpal tunnel syndrome. Issue 6 (3rd December 2013) - De Franco, P.; Erra, C.; Granata, G.; Coraci, D.; Padua, R.; Padua, L.
ABSTRACT Bifid median nerve is an anatomic variation that occurs in about 18% of patients with symptoms suggestive of carpal tunnel syndrome and in about 15% of symptom‐free subjects. Reversed palmaris longus is a rare anatomic muscular variation. The simultaneous presence of a bifid median nerve and a reversed palmaris longus has been very rarely described, usually during surgical exploration or in cadavers. We present two cases where ultrasound showed the presence of both abnormalities, allowing a correct diagnosis and influencing the treatment plan. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:371–374, 2014